IMPLEMENTATION OF FAMILY CENTERED CARE (FCC) BY HEALTH PERSONNEL - Ratnasari; Dwi Fitriyanti (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
The role of the family in the theoretical system is as a caregiver for sick family members. Family involvement in client care is applied in care known as the Family Centered Care concept. The application of Family Centered Care can increase knowledge and attitudes of families in the care of clients who are hospitalized. The purpose of the study was to determine the level of application of Family Centered Care. The research method used is a descriptive study. The research sample was 100 respondents. The sampling technique used is accidental sampling. The data collection tool used is a family centered care questionnaire. The research analysis used univariate analysis in the form of a frequency distribution. The results showed that the application of family centered care was in the good category as many as 71 respondents (71%), and in the medium category as many as 29 respondents (29%). From the results of the study, it was stated that nurses had involved the family in care, where the family participated in making decisions on support plans, recovery and helping patients not to be anxious. The conclusion is that the application of family centered care is in the good category.